Analisis Isi Pada Film “Miracle in Cell No. 7” Versi Indonesia Tentang Ketidakadilan Hukum - Arfian Suryasuciramdhan; Amanda Prisilia Nurmalita Sari; Fani Yulia Susyanti; Siti Mardianti; Siti Rohana (Student Scientific Creativity Journal, 2024)
The Indonesian version of the movie "Miracle in Cell No. 7" carries the theme of legal injustice that is very relevant to the lives of Indonesian people. Through message content analysis, this study discusses how the movie communicates messages about legal injustice through the story of Dodo Rozak, a mentally retarded father accused of murder. The analysis shows that the film uses effective storytelling strategies to portray legal injustice, including the use of sympathy and empathy towards Dodo Rozak, as well as the depiction of a corrupt and unfair legal system. The movie also features the struggle of Dodo and his daughter, Kartika, to get justice. Thus, this study shows that the Indonesian version of "Miracle in Cell No. 7" can be an effective tool to raise public awareness about the importance of justice and humanity in the legal system.